(untitled) (Zaporizhzhia Historical Review, 2021)
The article deals with the state of sugar industry in Naddnepryansky Ukraine in the middle of XIX century. The facts of sugar-refineries activities in Ukraine regions and in Russian state in the whole are quoted and analyzed there. The author comes to a conclusion that Ukraine gave 4/5 of all sugar production in Empire. Ukraine provided the internal market demand with sugar.